Internasionalisasi Praktik Permeabilitas Sistem Pendidikan Tinggi di Swiss - Hasanah, Eni Uswatun; Sassi, Komarudin (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This study aims to analyze the internationalization practices and permeability of the Swiss higher education system. Through a literature review and case studies, this research reveals how Switzerland has succeeded in building an open and inclusive higher education system for international students. The research results show that Switzerland has implemented various strategies to increase the permeability of its higher education system, including: (1) offering diverse and high-quality study programs in various languages, (2) facilitating the mobility of students and staff, (3) establishing collaborations with universities and research institutions throughout the world, and (4) creating a multicultural learning environment. This study concludes that the successful internationalization of the Swiss higher education system can be a model for other countries wishing to improve the quality and competitiveness of their higher education at the global level. However, further research is needed to identify the challenges and opportunities faced by Switzerland in maintaining and improving its position as an attractive study destination for international Student